2021
DOI: 10.3390/children8050411
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hippocampal Volume and Working Memory in 10,000+ 9–10-Year-Old Children: Sex Differences

Abstract: Aim: This study tested sex differences in the association between hippocampal volume and working memory of a national sample of 9–10-year-old children in the US. As the hippocampus is functionally lateralized (especially in task-related activities), we explored the results for the right and the left hippocampus. Methods: This is a cross-sectional study using the Adolescent Brain Cognitive Development (ABCD) Study data. This analysis included baseline ABCD data (n = 10,093) of children between ages 9 and 10 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…We identified that boys performed better than girls on the working memory task, which is inconsistent with the previous findings that women outperform men on visual working memory tests ( Harness et al, 2008 ) and no sex differences were found in verbal working memory ( Harness et al, 2008 ; Tulsky et al, 2014 ). However, our result was consistent with that in a prior ABCD paper ( Assari et al, 2021 ). These disparate findings demonstrate that sex differences in working memory performance differ in preadolescent children compared to adults ( Harness et al, 2008 ; Tulsky et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…We identified that boys performed better than girls on the working memory task, which is inconsistent with the previous findings that women outperform men on visual working memory tests ( Harness et al, 2008 ) and no sex differences were found in verbal working memory ( Harness et al, 2008 ; Tulsky et al, 2014 ). However, our result was consistent with that in a prior ABCD paper ( Assari et al, 2021 ). These disparate findings demonstrate that sex differences in working memory performance differ in preadolescent children compared to adults ( Harness et al, 2008 ; Tulsky et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Sex impacts the development of the brain, cognition, and behaviors. Sex differences in psychological cognitive well‐being, mental, and cognitive health outcomes (Assari, Boyce, & Jovanovic, 2021 ) and psychopathology (Loso et al, 2021 ) may originate from sex differences in brain structure and function in children. Several studies attempted to test the sex‐dependent structural and functional variations in the brains of males and females in youth (Satterthwaite et al, 2015 ; Sepehrband et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A review with meta-analysis discussed sex differences in sleep loss-induced cognitive deficits, with the majority of studies reporting greater impacts of sleep loss on cognitive health in women than in men ( 45 ). A more recent study tested sex differences in the association between hippocampal volume and working memory in a national sample of children 9 to 10 years old and reported larger bilateral hippocampal volumes in association with better working memory ( 46 ). Further, females vs. males showed stronger positive associations between the hippocampal volumes and working memory.…”
Section: Introductionmentioning
confidence: 99%